Structural analysis of the 1997 Mw 7.5 Manyi earthquake and the kinematics of the Manyi fault, central Tibetan Plateau. (1st August 2019) - Ren, Zhikun; Zhang, Zhuqi
Graphical abstract: Highlights: It is a comprehensive geological study on the 1997 Manyi rupture zone. The easternmost rupture extends ∼17 km in trends of N57°E, towards northeastward. The Manyi fault has the potential for propagating northeastward. A new block model is proposed for the BaryanHar block to fit its boundaries. Abstract: On 8th November 1997, the Mw 7.5 Manyi earthquake ruptured the left-lateral strike-slip Manyi fault in the central Tibetan Plateau. Despite its large magnitude, a comprehensive geological study on the co-seismic surface rupture has not yet been reported so far. Here we reported on our new results of the co-seismic surface ruptures and left-lateral offsets caused by the earthquake based on detailed interpretation of recently acquired high-resolution WorldView and SPOT-5 images. We recognized a primary ∼185-km-long surface rupture that trends N80°E, in consistence with previous results. Along the poorly developed segment at the eastern end of the Manyi fault, a new rupture is also identified, which trends N57°E and extends ∼17 km. The co-seismic surface rupture zone exhibits many distinct features such as stepovers, extensional cracks, ponds, restraining and releasing bends in relation to fault geometrical complexities. By visual analysis of the displaced geomorphic features using satellite imagery, we measured 198 co-seismic offsets along the ∼200 km fault trace. The results show a ∼3.7 m average offset and a maximum offset of up to ∼7.5 m near the epicenter area. The newly found ∼17-km-long rupture is interpreted to be linked to the main fault during the event. If the Manyi fault continues this northeastward propagation for additional 100 km, it will separate the BayanHar Block into two sub-blocks. Such a new hypothetical block model will influence assessment of seismic potential near the block boundaries and estimate of deformation of the BayanHar Block and the central Tibetan Plateau.